The NAD World 2.0: the importance of the inter-tissue communication mediated by NAMPT/NAD+/SIRT1 in mammalian aging and longevity control - Imai, Shin-ichiro (NPJ systems biology and applications, 2016)
The original concept of the NAD World was proposed in 2009, providing a comprehensive framework to investigate critical issues of biological robustness and trade-offs in mammalian aging and longevity control. Significant progress has been made over the past 7 years, advancing our understanding of the mechanisms by which biological robustness is maintained, and providing extensive support to the concept of the NAD World. Three key organs and tissues have been identified as basic elements in this control system for mammalian aging and longevity: the hypothalamus as the control center of aging, skeletal muscle as an effector, and adipose tissue as a modulator. While the hypothalamus sends a signal to skeletal muscle through the sympathetic nervous system, adipose tissue remotely regulates hypothalamic function by coordinating NAD + biosynthesis at a systemic level. Skeletal muscle might also communicate with other organs and tissues by secreting various myokines. The mammalian NAD + -dependent protein deacetylase SIRT1 and the key NAD + biosynthetic enzyme NAMPT mediate these inter-tissue communications. In this review, the function of each organ or tissue and their inter-tissue communications will be discussed in terms of understanding mammalian aging and longevity control. With such an emphasis on the system architecture, the concept is now reformulated as the NAD World 2.0, providing several important predictions. The concept of the NAD World 2.0 will provide a new foundation to understand a control system for mammalian aging and longevity and accelerate the development of an effective anti-aging intervention for humans.